Effect of egg shell powder (ESP) on cure characteristic, physical and mechanical properties of acrylonitrile rubber (NBR) composites / Noorakma Syareena Dahalan - Dahalan, Noorakma Syareena (2020)
Calcium Carbonate (CaCO3) is an inorganic powder that is usually used in paints, plastics and rubber industry as a filler. CaCO3 is used as a filler in some applications and studies have shown that egg shell contains about 95 % calcium carbonate. The objectives of this study are to study the characterization of treated Egg Shell (tES) and untreated Egg Shell (uES) powder in micron size by using Fourier-Transform Infrared Spectroscopy (FTIR). To determine the effect on cure characteristic of treated Egg Shell (tES) and untreated Egg Shell (uES) powder in NBR composites. To evaluate the physical and mechanical properties of treated Egg Shell (tES) and untreated Egg Shell (uES) powder in NBR composites. CaCO3 is derived from egg shell and undergoes pre-treatment which is alkali treatment. The egg shell undergoes specific process to make it as powder and being treated with 6 % concentration of Sodium Hydroxide (NaOH) to improve the Nitrile Rubber (NBR) composites performance. The treated egg shell (tES) is weighed based on the formulation compounding and divided into 5 phr, 10 phr, 15 phr and 20 phr of filler loading. Then, it was compounded with NBR and other ingredients. Besides, optimum loading of filler is determined. Hence, untreated egg shell (uES) and tES at optimum loading were compared the results. In addition of egg shell with different filler loading in the NBR composites, the cure characteristic, physical and mechanical properties of the composites are determined. For cure characteristic, tES was higher than uES which are 14 min and 12 min respectively. Meanwhile, for physical characteristic which is hardness, the higher result has been 52.25 which is tES due to the presence of NaOH coated in Egg shell powder (ESP). Besides, for crosslink density, tES had 6x10-4 while uES got 4x10-4. In the result of mechanical properties, tensile strength 2.51 MPa which is on tES was higher than uES. Then, for Young’s Modulus of tES also higher than uES, which is 4.94 MPa and 4.77 MPa respectively. Meanwhile, for elongation at break, tES got lower percentage than uES, which is 143.97 % and 190.97 %.